Level of knowledge on classification systems of malocclusions among dentists and orthodontists (2019)
Background: Malocclusion is the third dental public health problem by the World Health Organization. A classification of the patient’s occlusal traits should be performed to group them for better information management and to facilitate communication between specialists. Purpose: The aim of this study was to compare knowledge on classification systems of existing malocclusions among dentists and orthodontists. Materials and Methods: This research was a cross‑sectional study. A sample size of 239 general dental practitioners and 111 orthodontists was surveyed. Inclusion criteria were at least 1 year of work experience and location in the metropolitan area of Medellín. Individuals who were teachers were excluded. The questionnaire consisted of photographs of side and front dental study models of five patients in orthodontic clinic. Practitioners were asked to indicate both a diagnosis and the classification system used for their diagnosis. The percentage of correct answers provided was calculated for each stratified case by orthodontists and dentists and by the college from which they had graduated. Results: Of a total of 831 questionnaires distributed, 350 were filled out and returned. Most practitioners were diagnosed only in the sagittal plane, and 100% of responses used Angle’s classification. Vertical and transverse planes were considered when the occlusion alteration was highly pronounced. The percentage of correct answers was similar among universities. Conclusion: Classification systems of existing malocclusions do not provide the dentist or the orthodontist with appropriate occlusal diagnosis unless alterations are evident.